Juridical Review of the Decision on the Crime of Online Fraud against Job Vacancies - Dirman, Martianus; Cornelis, Vieta Imelda (Journal of Law and Social Politics, 2024)
Background: The rapid development of information technology has significantly increased the incidence of online fraud, including fraud related to job vacancies. This phenomenon has reached an alarming level and poses serious legal and social challenges, particularly in ensuring legal protection for victims and effective law enforcement against perpetrators. Objective: This study aims to identify the factors contributing to the occurrence of online fraud crimes related to job vacancies and to analyze the efforts undertaken by law enforcement authorities to prevent and address such crimes. Methods: This research employs a normative juridical approach by examining primary and secondary legal materials, including legislation, court decisions, and relevant legal literature. The analysis focuses on legal norms governing fraud crimes and law enforcement practices in addressing online fraud cases. Results: The findings indicate that online fraud crimes are influenced by economic, environmental, and socio-cultural factors, as well as the ease of committing online fraud and the relatively low risk of detection. Law enforcement efforts to combat online fraud include preventive measures such as public legal awareness campaigns, increased supervision of online transactions, and dissemination of warnings through media platforms, as well as repressive measures in the form of investigation, prosecution, sentencing, and correctional rehabilitation of offenders. Conclusion: Online job vacancy fraud requires comprehensive legal handling through a combination of preventive and repressive strategies. Strengthening law enforcement, increasing public awareness, and improving caution among online users are essential to reduce the incidence of online fraud crimes.